Advances in hospitality and leisure. Vol. 7 - Chen, Joseph S. (Bingley, U.K. : Emerald, 2011)
Advances in Hospitality and Leisure (AHL), a peer-review series published annually, is seeking to deliver refreshing insights from a host of scientific investigations pertaining to hospitality, leisure, and tourism while rendering an academic forum to stimulate discussion on current literature, contemporary issues and emerging trends essential to theory advancement as well as professional practices from a global perspective. The main focus of this series is to divulge the innovative methods of inquiry so as to inspire new research topics that are vital and have been in large neglected. AHL strives to address the needs of the populace willing to disseminate seminal ideas, concepts, and theories derived from scholarly inquiries. Potential readers may retrieve useful texts helping outline new research agendas, suggest viable topics for a dissertation work, and augment the knowledge of the new subjects of learning.
Exploring success factors in top careers in the Netherlands / Jenny M.H. Sok, Rob J. Blomme, Debbie M. Tromp, Jaap J. Van Muijen -- Achieving a coordination framework of strategy and information technology / David Y. Chang -- Safari tourism : a case study on tourist loyalty / Wen-Xi Chen, Wu-Chung Wu, Tzung-Cheng TC Huan -- Trouble in paradise? : the impact of changes to the working backpacker market to a regional destination / Alana Harris, Bruce Prideaux -- The behavior of Hong Kong cross-border shoppers : a nonparametric approach / Tak Kee Hui, Ho-Fuk Lau -- Psychological contract and organizational citizenship behavior : a new deal for new generations? / Xander D. Lub, Rob J. Blomme, P. Matthijs Bal -- The effects of nonresidents' geographical and cultural distance on a tourist destination's image / Zaher Hallab, Kyungmi Kim -- Examining the relationship between push and pull factors through partial least-squares path modeling / Mehmet Mehmetoglu -- Creating loyalty by involvement among festival goers / Hsing-Jung Tsai, Shih-Shuo Yeh, Tzung-Cheng TC Huan -- Sustainable tourism & hospitality management education : an empirical study on educational experiences in preparation for professional life / Willy Legrand, Philip Sloan, Rosemarie Delgado-Krebs, Heli Tooman -- Institutional holdings and corporate social responsibility in the hospitality industry / Seonghee Oak, Michael C. Dalbor.
Includes index.
Mode of access: World Wide Web.
Keywords: Hospitality industry; Leisure industry; Tourism